Surgical treatment of fracture in the anterior table of the frontal sinus (Research, Society and Development, 2020)
Introduction: The importance of the correct clinical and tomographic diagnosis of facial fractures is extremely important for the correct treatment, minimizing the chances of long and short term complications. Case report: Patient victim of severe trauma who underwent surgery to reconstruct the anterior wall of the frontal bone, evolving without complications and without aesthetic defects due to the correct treatment and approach of the case. Discussion: The computed tomographic and clinical examination together with the correct choice of treatment avoids complications that, when fractured in a region so close to the brain, becomes extremely important. Complications of difficult treatment and solution such as abscesses and osteomyelitis in such a region. Conclusion: The correct observation of the important anatomical structures in each fracture allows the correct and complete treatment with the minimized risk of complications or sequelae.